Omnichannel E-SPMB Marketing In SPMB Registration Strategy Management: A Study of The Effectiveness Digital Channel Integration in High School - Indra Puspita Sari; Nurul Zuriah; Arina Restian (Jurnal Pendidikan Indonesia, 2026)
The decline in the number of new students is a problem faced by a number of schools due to the suboptimal use of digital media as a means of promotion and student admission services. In addition, the New Student Admission System (SPMB) process is not yet digitally integrated, resulting in less effective information dissemination, registration processes, and student data management. This study aims to analyze, develop, and evaluate the design and implementation of omnichannel E-SPMB as a digital channel integration strategy to support the effectiveness of SPMB. This study uses the Research and Development (R&D) method with the ADDIE model development design. The research subjects consisted of 2 expert validators, namely 1 material expert and 1 media expert, as well as trial subjects involving 1 school principal and 1 SPMB team leader. Data were collected through observation, interviews, expert validation questionnaires, and user response questionnaires using observation guidelines, interview guidelines, and questionnaire sheets. Data analysis used quantitative descriptive techniques, qualitative descriptive techniques, and Paired Sample t-tests. The results of the study indicate that omnichannel E-SPMB has a very high level of validity and demonstrates significant effectiveness in increasing the ease of promotion, registration, and integration of SPMB digital services. Thus, omnichannel E-SPMB can be an alternative strategy for adaptive digital-based student admission management and contribute to increasing the effectiveness of educational services.